Role of automated detection of respiratory related heart rate changes in the diagnosis of sleep disordered breathing - Maresh, Scott; Athikumar, Adhithi Keerthana; Ahmed, Nabila; Chandu, Shivapriya; Prowting, Joel L.; Tumah, Layth; Najjar, Abed A.; Khan, Hamza; Sankari, Muna; Lasisi, Oluwatobi; Ravelo, Laurel A.; Peppard, Paul E.; et al. (Frontiers in Sleep, 2023)
Study Objectives: The objective of this study was to determine whether electrocardiogram (ECG) and heart rate accelerations that occurred in the vicinity of respiratory events could predict the severity of sleep-disordered breathing (SDB). Methods: De-identified polysomnogram (NPSG) recordings from 2091 eligible participants in the Sleep Heart Health Study (SHHS) were evaluated after developing and validating an automated algorithm using an initial set of recordings from 1438 participants to detect RR interval (RRI) dips in ECG and heart rate accelerations from pulse rate signal. Within-subject comparisons were made between the apnea-hypopnea index (AHI) and both the total RRI dip index (total RRDI) and total heart rate acceleration index (total HRAI). Results: The estimated AHIs using respiratory-related HRAI correlated with NPSG AHI both in the unadjusted and adjusted model (B: 0.83, and 0.81, respectively P<0.05). Respiratory-related HRAI had a strong agreement with NPSG AHI (intraclass correlation coefficient-ICC: 0.64, whereas respiratory-related RRDI displayed weaker agreement and ICC: 0.38). Further assessment of respiratory-related HRAI ( ≥5 /h) showed a strong diagnostic ability (78%, 87%, 8%1 and 56% agreement for traditional AHI cutoffs 5, 10, and 15 , and 30 events/h, respectively) At AHI cutoff of 5 events/h the receiver operating curves (ROC) revealed area under the curve (AUCs) of 0.90 and 0.96 for RE RRDI and RE HRAI respectively. Conclusion: The automated respiratory-related heart rate measurements derived from pulse rate provide an accurate method to detect the presence of SDB. Therefore, the detection of respiratory-related heart rate changes from pulse rate may enable an additional method to diagnose SDB.